Safinamide: an add-on treatment for managing Parkinson’s disease - Müller T (Dove Medical Press, 2018)
Thomas Müller Department of Neurology, St. Joseph Hospital Berlin-Weißensee, Berlin, Germany Abstract: Heterogeneous expression of neurotransmitter deficits results from onset and progression of Parkinson’s disease. Intervals, characterized by reappearance of motor and associated certain nonmotor symptoms, determine the end of good tolerability and efficacy of oral levodopa therapy. These “OFF” states result from levodopa pharmacokinetics and disease progression-related deterioration of the central buffering capacity for fluctuations of dopamine levels. This review discusses safinamide as an add-on therapeutic agent in orally levodopa-treated patients with “OFF” phenomena. Safinamide provided beneficial effects on “OFF” symptoms in pivotal trials with doses of 50 or 100 mg once daily. Safinamide reversibly inhibits monoamine oxidase B and declines abnormal glutamate release by modulation of potassium- and sodium ion channels. An ideal candidate for combination with safinamide is opicapone. This inhibitor of peripheral catechol-O-methyltransferase supports continuous brain delivery of levodopa and, thus, the continuous dopaminergic stimulation concept. Both compounds with their once-daily application and good tolerability may complement each other by reduction of necessary oral levodopa intakes and “OFF” times. Thus, a promising, future option will be combination of safinamide and opicapone in one formulation. It will reduce adherence issues and may complement levodopa treatment. It will probably cause less nausea and edema than a dopamine agonist/levodopa regimen. Keywords: safinamide, MAO-B inhibition, abnormal glutamate release inhibition, Parkinson’s disease, dopamine substitution, glutamate